Willa Cather and material culture : real-world writing, writing the real world - Stout, Janis P. (Studies in American literary realism and naturalism., 2005)
Thes 11 essays address Willa Cather's work and career through the lens of cultural studies. One of the volume's primary purposes is to demonstrate the extent to which Cather did participate in her culture and to correct the commonplace view of her as a literary connoisseur set apart from her times.